1990
DOI: 10.1523/jneurosci.10-11-03583.1990
|View full text |Cite
|
Sign up to set email alerts
|

Changes in instrumentally and classically conditioned limb-flexion responses following inferior olivary lesions and olivocerebellar tractotomy in the cat

Abstract: Lesions were placed in various parts of the inferior olivary nucleus and olivocerebellar tract in an attempt to define further the role of the inferior olive in the performance of a conditioned limb-flexion response (LFR) in cats. Thirty-two cats were trained to make an LFR using either classical or instrumental conditioning. The conditioned stimulus (CS) was a tone, and the unconditioned stimulus (US), a shock to the forelimb. Following training, lesions were placed in various parts of the inferior olivary nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…The present study demonstrates for the first time that cerebellar circuits are involved in TAL, as in other types of learning such as motor learning (Rondi-Reig, Delhaye-Bouchaud, Mariani, & Caston, 1997), conditioning of the patellar reflex in cats (Voneida, Christie, Bogdanski, & Chopko, 1990), conditioning of the nictitating membrane in rabbits (McCormick et al, 1985;Mintz et al, 1994), and others. Similarly, these studies have consistently demonstrated that electrolytic and chemical lesions in the inferior olive complex have suppressed previously established conditioned responses and prevented acquisition of new CRs (McCormick et al, 1985;Mintz et al, 1994).…”
Section: Discussionsupporting
confidence: 53%
“…The present study demonstrates for the first time that cerebellar circuits are involved in TAL, as in other types of learning such as motor learning (Rondi-Reig, Delhaye-Bouchaud, Mariani, & Caston, 1997), conditioning of the patellar reflex in cats (Voneida, Christie, Bogdanski, & Chopko, 1990), conditioning of the nictitating membrane in rabbits (McCormick et al, 1985;Mintz et al, 1994), and others. Similarly, these studies have consistently demonstrated that electrolytic and chemical lesions in the inferior olive complex have suppressed previously established conditioned responses and prevented acquisition of new CRs (McCormick et al, 1985;Mintz et al, 1994).…”
Section: Discussionsupporting
confidence: 53%
“…The critical region of the IO for eyeblink conditioning is the dorsal accessory olive (DAO), which receives predominantly somatosensory input relayed from the spinal cord and appropriate cranial nuclei, including nociceptive input (Brodal 1981). Lesions of the critical region of the IO, the face representation in the DAO, completely prevent learning if made before training and result in extinction of the CR if made after training (McCormick et al 1985;Voneida et al 1990 Yeo et al 1986). Neurons in this critical DAO region do not respond to auditory stimuli (CS), respond only to US onset, and show no learning-related activity, and the US-evoked response decreases as animals learn .…”
Section: The Us Pathwaymentioning
confidence: 99%
“…Although this region of the interpositus does project to the IO, as well as downstream targets, it does not appear that the IO is the site of memory formation or storage itself. Localized lesions of this region result in gradual extinction of the CR, as the IO is the essential relay for US information to the cerebellum (McCormick et al 1985;Voneida et al 1990). Large lesions and inactivation of the IO may result in immediate disruption of CR expression (Yeo et al 1986;Welsh and Harvey 1998), due in part to a resultant increase in the simple spike activity of Purkinje cells (Colin et al 1980;Montarolo et al 1982;Savio and Tempia 1985).…”
Section: The Us Pathwaymentioning
confidence: 99%
“…Over the course of training, this evoked unit response gradually disappears in inverse correlation with the development of behavioral CRs (Sears and Steinmetz 1991). Lesions of the critical region of the inferior olive, the face representation in the DAO, completely prevent learning if made before training, and result in extinction of the CR with continued paired training made after training (McCormick et al 1985;Voneida et al 1990, limb flexion in cat; Mintz et al 1994). Neurons in this critical DAO region do not respond to auditory stimuli (CS), respond only to US onset, and show no learning-related activity.…”
Section: Cold Spring Harbor Laboratory Press On May 11 2018 -Publishmentioning
confidence: 99%